Draft genome sequence of Acidihalobacter ferrooxidans DSM 14175 (strain V8), a new ironand sulfur-oxidizing, halotolerant, acidophilic species - Khaleque, H.; Ramsay, Joshua; Murphy, R.; Kaksonen, A.; Boxall, N.; Watkin, E. (American Society for Microbiology, 2017)
Â© 2017 Khaleque et al. The use of halotolerant acidophiles for bioleaching provides a biotechnical approach for the extraction of metals from regions where high salinity exists in the ores and source water. Here, we describe the first draft genome of a new species of a halotolerant and iron- and sulfur-oxidizing acidophile, Acidihalobacter ferrooxidans DSM 14175 (strain V8).